Does imagery work? Effects on performance and mental skills - Weinberg, R. (Journal of Imagery Research in Sport and Physical Activity, 2008)
This paper provides a review of the literature on the relationship between imagery and sport performance as well as between imagery and the development of mental skills. First, the many anecdotal reports of imagery effectiveness are noted and a definition is provided focusing on the multidimensional nature of imagery. The evidence of the enhancing influence of imagery on sport performance is then examined by looking at the early studies (mental practice), case studies, preparatory imagery, imagery used as part of a mental training package, and the use of imagery by successful athletes. After discussing the limitations in research imagery relating to performance, the focus turned to the relationship of imagery and the development of mental skills (e.g., confidence, dealing with pressure, motivation). Factors affecting imagery effectiveness were highlighted including imagery perspective, type of task, positive versus negative imagery, and timing of imagery. The paper concluded with future directions for research including such areas as amount of time to image, imagery and children, imagery ability, and imagery and performance expertise.